2011
DOI: 10.1007/s10237-011-0319-x
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of intermittent and continuous fluid shear stresses on osteogenic differentiation of human mesenchymal stem cells

Abstract: A reasonable mechanical microenvironment similar to the bone microenvironment in vivo is critical to the formation of engineering bone tissues. As fluid shear stress (FSS) produced by perfusion culture system can lead to the osteogenic differentiation of human mesenchymal stem cells (hMSCs), it is widely used in studies of bone tissue engineering. However, effects of FSS on the differentiation of hMSCs largely depend on the FSS application manner. It is interesting how different FSS application manners influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 43 publications
(51 reference statements)
3
44
1
Order By: Relevance
“…This is facilitated through the use of highly porous scaffold architectures, which enable nutrient and metabolite diffusion throughout, while also contributing to the shape and mechanical integrity of the tissue defect. Mechanical stimulation, in the form of fluid perfusion and mechanical compression, have been shown to play an important role in enhancing tissue regeneration and also directing the cellular fate of mesenchymal stem cells (MSCs) (Angele et al 2004;Delaine-Smith and Reilly 2012;Jaasma and O'Brien 2008;Keogh et al 2011;Liu et al 2012b;Miyashita et al 2014; Thompson et al 2010). For example, osteogenic differentiation of MSCs is prompted under mechanical stimulation, as indicated by the increase of Alkaline Phosphatase (ALP), Prostaglandin E 2 (PGE 2 ) expression and mineralisation (Bancroft et al 2002;Grayson et al 2008;Vance et al 2005;Yu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is facilitated through the use of highly porous scaffold architectures, which enable nutrient and metabolite diffusion throughout, while also contributing to the shape and mechanical integrity of the tissue defect. Mechanical stimulation, in the form of fluid perfusion and mechanical compression, have been shown to play an important role in enhancing tissue regeneration and also directing the cellular fate of mesenchymal stem cells (MSCs) (Angele et al 2004;Delaine-Smith and Reilly 2012;Jaasma and O'Brien 2008;Keogh et al 2011;Liu et al 2012b;Miyashita et al 2014; Thompson et al 2010). For example, osteogenic differentiation of MSCs is prompted under mechanical stimulation, as indicated by the increase of Alkaline Phosphatase (ALP), Prostaglandin E 2 (PGE 2 ) expression and mineralisation (Bancroft et al 2002;Grayson et al 2008;Vance et al 2005;Yu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that mechanical stimulation enhances bone tissue regeneration in vitro to a certain extent (Sittichockechaiwut et al 2009;Jaasma et al 2008;Goldstein et al 2001). In particular, it has been shown that osteogenic differentiation, as indicated by ALP, COX 2 and PGE 2 expression (Thompson et al 2010;Keogh et al 2011;Liu et al 2012), is enhanced when bone cells are exposed to the fluid flow, compared to static culture (Jaasma et al 2008;Goldstein et al 2001;Li et al 2009). Such changes could be related to the enhanced nutrient transport or mechanical stimulation of the cells within the scaffolds, but the precise nature of such changes is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…126 In perfusion chambers, oscillating fluid flow provided better mechanical signaling compared to the unidirectional counterpart. 127,128 Nevertheless, such bioreactor requires cell adhesion to exogenous surface, whereas cell surface adhesion may change the properties of aggregates. Alternatively, bi-axial wavy-walled bioreactors provided modular and more homogeneous shear stress compared to the uniaxial counterpart, which could be a flexible and scalable system for MSC aggregates.…”
Section: D Msc Aggregates: Mechanisms Properties and Applicationsmentioning
confidence: 99%